IgM-enriched Human Intravenous Immunoglobulin for Treatment of Early Antibody Mediated Rejection after Heart Transplantation. (July 2018) - Barten, Markus J; Buchholz, Christian; Bernhardt, Alexander; Rybczynski, Meike; Grahn, Hanno; Reichenspurner, Hermann
Abstract : Introduction: Early antibody mediated rejection (AMR) is a risk factor for decreased survival after heart transplantation (HTx). IgM-enriched immunoglobulin (IgGAM) effectively treated early donor-specific antibodies (DSA) against human leukocyte antigen (HLA) following lung transplantation. Here we describe our first results on treatment of early post-HTx AMR with IgGAM. Case Reports: Prior HTx, our first patient (38 years old) suffered from giant cell myocarditis, and our second patient (44 years old) had left ventricular assist device therapy for 3.5 years. Initial course of HTx was uneventful besides a successful therapy of cytomegaly virus infection in the older patient. In the third week surveillance endomyocardial biopsies (EMBs) showed a pAMR2 (ISHLT 2013) without acute cellular rejection (ACR, ISHLT 0R) in both patients. Interestingly, both patients developed non-DSA against HLA class II. However, echocardiography showed a normal graft function, and, therefore, we treated each patients only with a cumulative dose of 30g of IgGAM. At month three post-HTx EMBs showed no AMR or ACR in both patients. In general, treatment strategies for AMR are directed at inhibiting the humoral response at various levels by targeting removal and blockade of circulating antibodies, depletion of B cells and plasma cells, suppression of T cells-dependent antibody responses, and inhibition of the complement cascade. Intravenous immunoglobulins containing solely IgG cover many of these strategies. However, compared to the IgG immunoglobulins, IgGAM has the advantage that the content of IgM is 10x stronger in complement inhibition. Moreover, research studies show the importance of a normal IgM serum level in the induction of B cell tolerance.Conclusion Our two cases indicate that patients with early AMR and non-DSA against HLA class II but normal graft dysfunction may profit from early intervention with IgGAM. Thus, further studies need to confirm the role of IgGAM in the treatment strategy of AMR, and to explore the role of serum IgM levels in the pathogenesis of developing alloantibodies and AMR.